Mortality, morbidity and economic growth. - Lorenzo Rocco (Public Library of Science (PLoS), 2021)
The question of whether and how changes to population health impact on economic growth has been actively studied in the literature, albeit with mixed results. We contribute to this debate by reassessing-and extending-[1], one of the most influential studies. We include a larger set of countries (135) and cover a more recent period (1990-2014). We also account for morbidity in addition to mortality and adopt the strategy of providing bounding sets for the effects of interest rather than point estimates. We find that reducing mortality and disability adjusted life years (DALYs), a measure which combines morbidity and mortality, promotes per capita GDP growth. The magnitude of the effect is moderate, but non negligible, and it is similar for mortality and DALYs.